# Factorization by Grouping

Factorization by grouping means that we need to group the terms with common factors before factoring.

Method of factorization by grouping the terms:

(i) From the groups of the given expression a factor can be taken out from each group.

(ii) Factorize each group

(iii) Now take out the factor common to group formed.

Now we will learn how to factor the terms by grouping.

Solved examples of factorization by grouping:

1. Factor grouping the expressions:

1 + a + ac + a2c

Solution:

1 + a + ac + a2c

= (1 + a) + (ac + a2c)

= (1 + a) + ac (1 + a)

= (1 + a) (1 + ac).

2. How to factor by grouping the following algebraic expressions?

(i) a2 - ac + ab - bc

Solution:

a2 - ac + ab - bc

= a(a - c) + b(a - c)

= (a - c) (a + b)

Therefore, by factoring expressions we get (a - c)(a + b)

(ii) a2 + 3a + ac + 3c

Solution:

a2 + 3a + ac + 3c

= a(a + 3) + c(a + 3)

= (a + 3) (a + c)

Therefore, by factoring expressions we get (a + 3)(a + c)

3. Factorize the algebraic expressions:

(i) 2x + cx + 2c + c2

Solution:

2x + cx + 2c + c2

= x(2 + c) + c(2 + c)

= (2 + c) (x + c)

(ii) x2 - ax + 5x - 5a

Solution:

x2 - ax + 5x - 5a

= x(x - a) + 5(x - a)

= (x - a) (x + 5)

(iii) ax - bx - az + bz

Solution:

ax - bx - az + bz

= x(a - b) - z(a - b)

= (a - b) (x - z)

(iv) mx - 2my - nx + 2ny

Solution:

mx - 2my - nx + 2ny

= m(x - 2y) - n(x - 2y)

= (x - 2y) (m - n)

(v) ax2 - 3bxy – axy + 3by2

Solution:

ax2 - 3bxy – axy + 3by2

= x(ax – 3by) – y(ax – 3by)

= (ax - 3by) (ax - y)

4. Factor each of the following expressions by grouping:

(i) x2 - 3x - xy + 3y

Solution:

x2 - 3x - xy + 3y

= x(x – 3) – y(x – 3)

= (x – 3) (x – y)

(ii) ax2 + bx2 + 2a + 2b

Solution:

ax2 + bx2 + 2a + 2b

= x2(a + b) + 2(a + b)

= (a + b) (x2 + 2)

(iii) 2ax2 + 3axy - 2bxy - 3by2

Solution:

2ax2 + 3axy - 2bxy - 3by2

= ax(2x + 3y) - by(2x + 3y)

= (2x + 3y) (ax - by)

(iv) amx2 + bmxy – anxy – bny2

Solution:

amx2 + bmxy – anxy – bny2

= mx(ax + by) – ny(ax + by)

= (ax + by) (mx – ny)

5. Factorize:

(i) (x + y) (2x + 5) - (x + y) (x + 3)

Solution:

(x + y) (2x + 5) - (x + y) (x + 3)

= (x + y) [(2x + 5) - (x + 3)]

= (x + y) [2x + 5 - x -3]

= (x + y) (x + 2)

(ii) 6ab - b2 + 12ac - 2bc

Solution:

6ab - b2 + 12ac - 2bc

= b(6a - b) + 2c(6a - b)

= (6a - b) (b + 2c)

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles 1. ### Months of the Year | List of 12 Months of the Year |Jan, Feb, Mar, Apr

Dec 01, 23 01:16 AM

There are 12 months in a year. The months are January, February, march, April, May, June, July, August, September, October, November and December. The year begins with the January month. December is t…

2. ### Days of the Week | 7 Days of the Week | What are the Seven Days?

Nov 30, 23 10:59 PM

We know that, seven days of a week are Monday, Tuesday, Wednesday, Thursday, Friday, Saturday, Sunday. A day has 24 hours. There are 52 weeks in a year. Fill in the missing dates and answer the questi…